Radial polarization imaging of entangled biphoton state - Jiung Kim; Jeeseong Hwang; Martin Y. Sohn (APL Photonics)
Polarization entanglement of single photons is a key element to enable quantum 2.0 applications, such as quantum computing, quantum networks, and quantum sensing. Verification and fidelity assessment of the entanglement state are typically performed by sequential coincidence measurements with single-pixel photon detectors. Quantum imaging techniques that use single-photon imaging cameras for visualizing an entangled biphoton state and calculating Bell’s inequality have been reported. Their performances are limited for practical use due to low photon flux and low speed. Here, we introduce a new approach to image polarization-entangled biphoton states using radial polarizations, which enables rapid high-performance entanglement measurement. An intensified single-photon counting camera (SPCC) captures a single image with multiple polarizations imposed by a radial wave plate, which converts a linear polarization of single photons to radial polarizations. The coincidence photon image is rapidly taken with the SPCC in the integrate-on-chip mode, which is triggered by the idler photons set at a specific polarization angle. Bell’s inequality is calculated directly from four coincidence images that show polarization correlation. Our technique not only visualizes the entangled polarization state but also enables fast full Bell-type evaluation of photonic polarization entanglement. We envision that our approach may be instrumental for developing advanced polarization-entangled photon sources and polarization-entangled quantum systems, which in turn would advance fundamental research involving dynamic photon–matter interactions.